Comparative effect of tomato juice, walking, and their combination on blood pressure in prehypertension - Jane Christofanie; Budi Setiawan; Mira Dewi (AcTion: Aceh Nutrition Journal, 2025)
This study examined the individual and combined effects of tomato juice and increased daily walking on blood pressure in prehypertensive adults. A total of 34 sedentary participants aged 19–36 years were randomly assigned to four groups: control, tomato juice, walking, and a combination of both. The intervention lasted for 14 days, during which participants consumed 200 ml of unsalted tomato juice and/or increased their steps by a minimum of 5,000 steps per day (on average), tracked using health (iOS) or Google Fit (Android). Blood pressure was measured before and after the intervention and analyzed using paired t-tests (p<0,05). All intervention groups showed a reduction in systolic blood pressure, with the combination group showing the most significant decrease—from 128,75±4,20 to 110,50±6,05 mmHg (p=0,000) for systolic and from 82,50±8,40 to 74,74±3,92 mmHg (p=0,033) for diastolic pressure. A significant correlation between body mass index and blood pressure reduction was also observed, suggesting that body weight may influence the effectiveness of these lifestyle interventions.